Implementation of an Early Childhood Healthy Eating and Physical Activity Program in New South Wales, Australia: Munch & Move - Green, Amanda M.; Mihrshahi, Seema; Innes-Hughes, Christine; O'Hara, Blythe J.; McGill, Bronwyn; Rissel, Chris (Frontiers in Public Health, 2020)
Background: Childhood obesity is an important public health issue. Approximately 20% of 2-4 year olds are overweight or obese, meaning 1 in 5 Australian children start school above a healthy weight. In the state of New South Wales (NSW) the combined prevalence of childhood overweight and obesity is significantly higher among children from low socioeconomic status backgrounds and children from regional, rural and remote areas. This paper describes implementation of a healthy eating and active play program (Munch & Move) for centre-based early childhood education and care (ECEC) services aimed at influencing healthy behaviours in young children in NSW, Australia. It shows changes over time including access by disadvantaged, Aboriginal and remote communities and outlines some of the challenges and future opportunities for the program. Methods: Routine data in relation to service delivery (reach) and implementation indicators are collected by Local Health District staff. Fifteen implementation indicators (known as practices) were introduced to monitor the implementation of Munch & Move. Results: As of 30 June 2017, 88.4% of ECEC services have staff trained in Munch & Move. Of the 15 practices related to promoting and encouraging healthy eating, increasing physical activity and improving the quality of service delivery 13 practices saw significant improvements between 2012 and 2017. This was consistent for services with a high proportion of Aboriginal children and for services in disadvantaged and remote communities. There has been a statistically significant increase in the proportion (37.6% to 81.0%) and type of ECEC services (preschools 36.1% to 81.3%), long day care 38.6% to 81.0% and occasional care 34.0% to 74.6%) that have implemented the program since 2012 as well as in services with a high proportion of Aboriginal children (33.6% to 85.2%), services in disadvantaged communities (37.4% to 83.3%) and services in remote communities (27.8% to 59.4%). Discussion: This paper demonstrates that Munch & Move has seen large improvements in the delivery of training, practice achievements and program adoption in ECEC services across NSW including services in disadvantaged and remote communities and that have a higher proportion of Aboriginal children.